2021
DOI: 10.1002/jsfa.11241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organic substrates in urban rooftop agriculture, towards improving crop production resilience to temporary drought in Mediterranean cities

Abstract: BACKGROUND: Urban agriculture contributes to meet food production demand in cities. In a context of low water availability, it is important to consider alternatives that are able to maintain production. This study aimed to assess the use of substrates made from local materials and high water retention capacity as an alternative for urban agriculture in periods with water stress. Different substrates were used for 3 consecutive crop cycles of lettuce (Lactuca sativa L.) during the spring and summer periods of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this case, it was carried out according to the activity of the main authors. Therefore, Figure 4 crop production resilience to temporary drought in Mediterranean cities" [60] is one of the investigations carried out by said authors; some of those that make up the purple cluster can also be found in this publication. The light blue and orange clusters are the smallest, with four and three authors, respectively.…”
Section: Most Prolific Authorsmentioning
confidence: 84%
“…In this case, it was carried out according to the activity of the main authors. Therefore, Figure 4 crop production resilience to temporary drought in Mediterranean cities" [60] is one of the investigations carried out by said authors; some of those that make up the purple cluster can also be found in this publication. The light blue and orange clusters are the smallest, with four and three authors, respectively.…”
Section: Most Prolific Authorsmentioning
confidence: 84%
“…kt, kilotons. 1 (Grillas et al 2001;Maher et al 2008;Papadopoulos et al 2008;Barrett et al 2016); 2 (Soil and Substrate Preparers Association 2020); 3, 5 (U.S. Geological Survey 2020); 4 (Growing Media Europe 2019); "a" only for Europe; "b" Coconut production…”
Section: Environmental Life Cycle Assessment (E-lca)mentioning
confidence: 99%
“…In this context, an array of growing media can be used for vegetable cultivation. These substances have to share features such as lightness, porosity and water retention capacity (Maher et al 2008;Papadopoulos et al 2008). In this case study, three constituents were analysed: perlite, peat and coir.…”
Section: Social Life Cycle Assessment (S-lca)mentioning
confidence: 99%
See 1 more Smart Citation